Pengaruh Penggunaan Aplikasi Belanja Online, Gaya Hidup dan Literasi Keuangan terhadap Perilaku Konsumtif Mahasiswa - Fadhilah, Nur; Abadi, Muhammad Taufiq (Universitas Bunda Mulia, 2023)
The purpose of this study was to determine the effect of using online shopping applications, digital payment applications, lifestyle, financial literacy and self-control on the consumptive behavior of FEBI students at UIN K.H. Abdurrahman Wahid Pekalongan class of 2019. This research is included in the type of field research or field research with a quantitative approach. The sampling technique used was proportional random sampling, followed by accidental sampling and data obtained based on the results of distributing questionnaires to FEBI students at UIN K.H. Abdurrahman Wahid Pekalongan class of 2019. The results showed that the use of online shopping applications partially had a positive and significant effect on student consumptive behavior. Digital payment applications partially have a negative and insignificant effect on student consumptive behavior. Lifestyle partially has a positive and significant effect on student consumptive behavior. Financial literacy partially has a negative and insignificant effect on student consumptive behavior. Partial self-control has a negative and significant effect on student consumptive behavior. Simultaneously the use of online shopping applications, digital payment applications, lifestyle, financial literacy and self-control have a positive and significant effect on student consumptive behavior.